Truth in criminal trial - Izydorczyk, Jacek (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
The article Truth in criminal trial points out great importance of facts in every criminal procedure. The author presents a new look at some legal regulations in Poland. For example he strongly criticizes laws (and practice!) which forbid disclosure of a criminal’s personal data. It is just unfair towards decent citizens because they might be future victims of such criminals. By the way: veritatem sequi est tueri iustitiam.